Anion exchange membrane and method for making same
By converting neutral precursor polymers into cationic polymers before membrane formation, the complexity of anion exchange membrane fabrication is reduced, enhancing process efficiency and solvent reuse.
Patent Information
- Application Number
- JP2024554622
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-14
- Filing Date
- 2023-02-09
- Publication Date
- 2025-04-15
AI Technical Summary
The fabrication of anion exchange membranes is challenging due to the need for multiple wet process steps to convert neutral precursor polymers into cationic polymers, which complicates the process and solvent reuse.
A method is developed where the neutral precursor polymer is converted into a cationic polymer prior to membrane formation, eliminating the need for post-formation wet processing steps and improving solvent capture and reuse.
This approach simplifies the membrane fabrication process, reduces the complexity of wet processing, and facilitates more efficient solvent management, leading to improved membrane production efficiency.
Smart Images

Figure 2025510611000001 
Figure 2025510611000002 
Figure 2025510611000003
Abstract
Description
[Background technology]
[0001] [Government Rights] This invention was made with United States Government support under Contract No. 5971-3M-DOE-8433. The Government has certain rights in this invention.
[0002] [Background technology] Anion exchange membranes are of interest for use in electrochemical cells. Anion exchange membranes are formed from polymers with cationic functional groups (i.e., cationic polymers). In this class of membranes, anions can migrate through the material while the cationic countercharge remains fixed on the polymer backbone. However, membranes are difficult to fabricate. Typically, a neutral precursor polymer containing pendant halogenated alkyl groups is dissolved in an organic solvent, coated onto a temporary substrate, and dried. This film is then immersed in a solution of an excess of a tertiary amine, forming pendant groups containing quaternary amino groups with halide counterions. Prior to use, the halide can be ion-exchanged with another counterion desired for the application. This process is undesirable because it requires coating from an organic solvent and multiple wet processing steps on the film before forming a membrane that is ready for use. Summary of the Invention
[0003] A method for making anion exchange membranes is provided. A neutral precursor polymer is converted to a cationic polymer prior to forming a membrane. The cationic polymer contains pendant groups that contain quaternary amino groups. This method of making anion exchange membranes eliminates the need to perform multiple wet process steps on the membrane after formation to convert the neutral precursor polymer to a cationic polymer. Furthermore, this method allows for improved solvent capture and ease of reuse compared to previous synthesis methods, since these steps are performed prior to membrane formation.
[0004] A method for preparing a membrane comprising a cationic polymer is provided, the membrane being capable of functioning as an anion exchange membrane, the method comprising: (a) providing a precursor polymer comprising x repeat units of formula (I) and y repeat units of formula (II). [ka] [ka] In formula (I), each R 1 is independently aralkyl or substituted aralkyl. In formula (II), each R 2 is independently an alkylene having at least 4 carbon atoms and each L is independently a leaving group. The variable x represents the total mole fraction of repeat units of formula (I) in the precursor polymer and the variable y represents the total mole fraction of repeat units of formula (II) in the precursor polymer. The method further includes (b) reacting the repeat units of formula (II) in the precursor copolymer with an amine compound that includes a tertiary amino group to form a cationic polymer having a plurality of cationic repeat units of formula (III). [ka] In formula (III), each R 3 is the formula {-[N(R 4 )2 + ]-R 5} v -[N(R 4 )3] + wherein each R 4 is alkyl, and each R 5 is alkylene. The variable v is an integer ranging from 0 to 10. Each asterisk (*) represents a point in the precursor polymer or cationic polymer where a repeat unit is attached to another repeat unit or to an end group. The method further includes (c) forming a dispersion comprising particles of the cationic polymer, (d) preparing a coating layer from the dispersion, and (e) drying the coating layer to form an anion exchange membrane comprising the cationic polymer.
[0005] As used herein, the terms "a," "an," and "the" are used interchangeably and mean one or more.
[0006] As used herein, the term "and / or" is used to indicate that either or both of the stated things can occur; for example, A and / or B includes (A and B) and (A or B). Thus, the term can be used to mean A only, B only, or both A and B.
[0007] As used herein, the term "anion exchange membrane" refers to a membrane comprising a cationic polymer that allows the selective transport of anions.
[0008] The term "polymer" as used herein refers to a polymer having a number average molecular weight (Mn) of at least 5,000 daltons, at least 10,000 daltons, at least 25,000 daltons, at least 50,000 daltons, at least 100,000 daltons, at least 300,000 daltons, at least 500,000 daltons, at least 750,000 daltons, at least 1,000,000 daltons, or even at least 1,500,000 daltons, and a reaction product of a plurality of monomers having ethylenically unsaturated groups. The term "polymer" includes homopolymers, copolymers, terpolymers, and the like. The term "copolymer" is often used herein to refer to a polymer having at least two different types of monomer units.
[0009] The term "repeating unit" refers to a monomeric unit within a polymer. For example, a repeating unit of formula (I) [ka] is the formula CH2=CHR 1 It is formed from the monomers:
[0010] As used herein, an asterisk (*) is used to indicate the point at which a repeat unit within a polymeric material is attached to another group within the polymeric material, for example, to another repeat unit or to an end group.
[0011] As used herein, the term "alkyl" refers to a substituted or unsubstituted monovalent radical of an alkane. The alkyl may be linear, branched, cyclic, or a combination thereof. The alkyl group often contains 1 to 40 carbon atoms. For example, the alkyl can have at least 1, at least 2, at least 3, at least 4, at least 6, at least 8, at least 10, at least 12, or at least 16 carbon atoms, and up to 40, up to 30, up to 20, up to 16, up to 12, up to 10, up to 8, up to 6, or up to 4 carbon atoms. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, isopropyl, iso-butyl, sec-butyl, t-butyl, neopentyl, isopentyl, 2-dimethylpropyl, and cyclohexyl.
[0012] As used herein, the term "alkylene" refers to a substituted or unsubstituted divalent radical of an alkane. The alkylene may be linear, branched, cyclic, or a combination thereof. The alkylene group often contains 1 to 40 carbon atoms. For example, the alkylene can have at least 1, at least 2, at least 3, at least 4, at least 6, at least 8, at least 10, at least 12, or at least 16 carbon atoms, and up to 40, up to 30, up to 20, up to 16, up to 12, up to 10, up to 8, up to 6, or up to 4 carbon atoms. Examples of alkylene groups include, but are not limited to, methylene, ethylene, n-propylene, n-butylene, n-pentylene, n-hexylene, n-heptylene, n-octylene, and cyclohexylene.
[0013] As used herein, the term "aryl" refers to a substituted or unsubstituted cyclic aromatic hydrocarbon that does not contain heteroatoms in the ring. Thus, aryl groups include, but are not limited to, phenyl, azulenyl, heptalenyl, biphenyl, indacenyl, fluorenyl, phenanthrenyl, triphenylenyl, pyrenyl, naphthacenyl, chrysenyl, biphenylenyl, anthracenyl and naphthyl groups. In some embodiments, the alkyl group contains about 6-14 carbon atoms, 6-12 carbon atoms, or 6-10 carbon atoms.
[0014] As used herein, the term "aralkyl" refers to an alkyl group substituted with an aryl group. An aralkyl can be considered an alkylene bonded to an aryl group. The alkylene can have 1 to 10 carbon atoms (e.g., at least 1, at least 2, at least 3, or at least 4 and up to 8, up to 6, or up to 4 carbon atoms) and the aryl group can have 6 to 10 carbon atoms (e.g., at least 6, at least 8, and up to 10, or up to 8). In some embodiments, the alkylene has 1 to 10 carbon atoms (e.g., 1 to 6 carbon atoms or 1 to 4 carbon atoms) and the aryl is phenyl. The aralkyl group can be substituted or unsubstituted.
[0015] As used herein, the term "substituted" refers broadly to a group (e.g., an alkyl, aryl, or aralkyl group) in which at least one hydrogen atom has been replaced with at least one "substituent." Examples of substituents include, but are not limited to, alkyl groups, halogens (e.g., F, Cl, Br, and I), and various oxygen-containing groups (wherein the oxygen atom is typically the atom that is linked to the group being substituted), such as hydroxyl, alkoxy, and aryloxy groups. Examples include aryl substituted with alkyl, alkoxy, or halo.
[0016] The terms “halo” or “halogen” or “halide,” by themselves or as part of another substituent, mean, unless otherwise stated, a fluorine, chlorine, bromine, or iodine atom or ion.
[0017] As used herein, the term "leaving group" refers to a group that can be displaced and replaced by a nucleophilic atom, such as a nitrogen atom. Examples of leaving groups include halogens, such as chlorine, bromine, and iodine (displaced as chloride, bromide, and iodide), and sulfonyl esters, such as mesyl, tosyl, and nosyl (displaced as mesylate, tosylate, and nosylate). Although the leaving group can be any suitable leaving group, the leaving group is often bromine.
[0018] As used herein, the term "anionic counterion" refers to an anion such as chloride, bromide, iodide, acetate, sulfate, carbonate, or bicarbonate. Anionic counterions also include mesylate, tosylate, nosylate, hydroxide, and alkoxide ions. Cationic polymers have anionic counterions to balance the charge of the cationic groups. Anionic counterions may be referred to herein as "counterions."
[0019] Further herein, the recitation of ranges by endpoints includes all numbers subsumed within that range (eg, 1 to 10 includes 1.4, 1.9, 2.33, 5.75, 9.98, etc.).
[0020] Further, as used herein, references to "at least one" include all numbers greater than or equal to one (e.g., at least 2, at least 4, at least 6, at least 8, at least 10, at least 25, at least 50, at least 100, etc.).
[0021] As used herein, the term "about" may allow for some variability in values or ranges, for example, within 10%, within 5%, or within 1% of a stated value or of the limits of a stated range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] A process for making anion exchange membranes is provided. In this method, a neutral (i.e., non-ionic) precursor polymer is converted to a cationic polymer having multiple quaternary amino groups. The cationic polymer is formed prior to the formation of the anion exchange membrane. This process is advantageous over conventional preparation methods in which a film is formed from the precursor polymer and then the cationic polymer is formed at a later time. Preparing the cationic polymer prior to film (e.g., membrane) formation advantageously eliminates the need for additional wet processing steps on the film to synthesize cationic groups. Additionally, solvent capture and reuse is facilitated by performing key reaction steps associated with the conversion of the precursor polymer to a cationic polymer prior to the formation of the anion exchange membrane.
[0023] The method includes preparing or providing a precursor polymer capable of being converted to a cationic polymer, the precursor polymer comprising x repeat units of formula (I) and y repeat units of formula (II). [ka] [ka] The variable x represents the total mole fraction of repeat units of formula (I) in the precursor polymer, and the variable y represents the total mole fraction of repeat units of formula (II) in the precursor polymer. The precursor polymer can be either a random or block copolymer, but is often a random copolymer. In formula (I), each R 1 is independently aralkyl or substituted aralkyl. In formula (II), each R 2is independently an alkylene having at least 4 carbon atoms, and each L is independently a leaving group.
[0024] R in formula (I) 1 is aralkyl or substituted aralkyl. The aryl portion of the aralkyl group is often phenyl, and the alkylene portion of the aralkyl group often has 2 to 6 carbon atoms, 2 to 4 carbon atoms, or 2 carbon atoms. The aryl portion can be optionally substituted with a substituent such as, for example, an alkyl (e.g., an alkyl having 1 to 6 or 1 to 4 carbon atoms), an alkoxy (e.g., an alkoxy having 1 to 6 or 1 to 4 carbon atoms), or a halogen (e.g., fluorine, bromine, chlorine, or iodine).
[0025] The variable x represents the total mole fraction of repeat units of formula (I) in the precursor polymer and in the subsequently formed cationic polymer. In some embodiments, the variable x ranges from 0.65 to 0.85. For example, the variable x is at least 0.65, at least 0.70, at least 0.75, or at least 0.80, and up to 0.85, up to 0.80, up to 0.75, or up to 0.70.
[0026] The sum of the variables x and y is often equal to 1. However, additional repeat units other than those of formulas (I) and (II) can be present. When other repeat units are present, the sum of x and y is typically at least 0.80, at least 0.85, at least 0.90, at least 0.95, at least 0.97, at least 0.98, or at least 0.99.
[0027] Each R in formula (II) 2 is an alkylene having at least 4 carbon atoms. The number of carbon atoms is often in the range of 4 to 20, e.g., at least 4, at least 5, at least 6, at least 8, or at least 10, and up to 20, up to 18, up to 16, up to 12, up to 10, or up to 8. In some embodiments, each R2 are independently represented by the formula -(CH2) n -group, where n is an integer from 6 to 12, for example, an integer in the range of 6 to 10, 8 to 12, or 8 to 10.
[0028] The group L in formula (II) is a leaving group. Although L can be any suitable leaving group as defined above, the leaving group is often a halogen, such as chlorine, bromine, or iodine, which is removed as chloride, bromide, and iodide ions when reacted with an amine compound. In many embodiments, L is bromine.
[0029] The variable y represents the total mole fraction of repeat units of formula (II) in the precursor polymer. In some embodiments, the variable y is in the range of 0.15 to 0.35. For example, the variable x is at least 0.15, at least 0.20, at least 0.25, or at least 0.30, and at most 0.35, at most 0.30, at most 0.25, or at most 0.20.
[0030] The precursor polymer can be prepared using any suitable method. In many embodiments, a Ziegler-Natta catalyst is used to polymerize the monomers used to form the precursor polymer. In such methods, the monomers are dissolved in a non-polar organic solvent, such as toluene, an alkane, xylene, or the like, or a combination thereof. A Ziegler-Natta catalyst is then added to the monomer-containing solution to form a reaction mixture. Any suitable Ziegler-Natta catalyst can be used. The catalyst can be, for example, titanium trichloride, titanium tetrachloride, vanadium tetrachloride, titanium metallocene (e.g., titanocene dichloride), zirconium metallocene, or a combination thereof. The catalyst is often used in combination with a cocatalyst or activator. For example, diethylaluminum chloride, triethylaluminum, or triisobutylaluminum chloride are often used as cocatalysts, which can be referred to as activators for use with titanium trichloride, titanium tetrachloride, or vanadium tetrachloride, and methylaluminoxane (MAO) is often used as a cocatalyst for use with titanium metallocene or zirconium metallocene.
[0031] Typically, the precursor polymer is initially formed as a gel-like polymer as the molecular weight increases. This gel-like polymer can be fully precipitated as the precursor polymer by the addition of an alcohol such as methanol. The precipitated precursor polymer material can be collected, crushed into small pieces, and dissolved in a non-polar solvent such as toluene for purification purposes. This additional step allows for easy removal of the catalyst and any residual monomers. The dissolved precursor polymer can then be precipitated again by the addition of an alcohol, such as methanol, ethanol, isopropanol, or mixtures thereof. The purified precursor polymer can then be collected and dried. Any suitable drying method can be used. For example, the precursor polymer can be dried under vacuum at a temperature ranging from about 20 degrees Celsius to about 75 degrees Celsius.
[0032] The method further comprises reacting the repeat unit of formula (II) of the precursor polymer with an amine compound with a tertiary amino group to form a cationic polymer having z repeat units of formula (III). [ka] In formula (III), each R 3 is the formula {-[N(R 4 )2 + ]-R 5} v -[N(R 4 )3] + wherein each R 4 is alkyl, and each R 5 is alkylene and the variable v is an integer ranging from 0 to 10. As with the repeat unit of formula (II), each asterisk (*) in formula (III) represents the point at which the repeat unit is attached to another repeat unit or to an end group in the cationic polymer. 3 has one or more corresponding anionic counterions to balance the charge of the cationic groups.
[0033] Each R 4 The group is an alkyl group. The alkyl group often has 1 to 10 carbon atoms. For example, the alkyl group can have at least 1, at least 2, at least 3, or at least 4, and up to 10, up to 8, up to 6, or up to 4 carbon atoms.
[0034] Each R 5 is alkylene. In most embodiments, the alkylene has 4 to 12 carbon atoms or 6 to 12 carbon atoms. For example, the alkylene can have at least 4, at least 6, at least 8, or at least 10, and up to 12, up to 10, or up to 8 carbon atoms.
[0035] The variable v ranges from 0 to 10, for example, 0, at least 1, at least 2, at least 3, or at least 4, and up to 10, up to 8, up to 6, up to 4, or up to 3. When v is 0, the group R 3 is -[N(R 4 )3] + That is, R 3 contains a single cationic group. Such groups are found in monomer units of formula (II) and in monomer units of formula N(R 4 )3 with a tertiary amine compound. 4 is often methyl, ethyl, or propyl (i.e., the tertiary amine compound is trimethylamine, triethylamine, or tripropylamine, respectively). In other embodiments, the group R 3 contains multiple cationic groups. For these groups, the formula [N(R 4 )2 + ]-R 5} v -[N(R 4 )3] + in which the variable v is an integer ranging from 1 to 10. Such groups include monomer units of formula (II) and formula N(R 4 )2-R 5 -{[N(R 4 )2 + ]-R 5} v-1 -[N(R 4 )3] + With a cationic amine. Any suitable counter anion may be present to balance the charge of the cationic group.
[0036] The formula N(R 4 )2-R 5 -{[N(R 4 )2 + ]-R 5} v-1 -[N(R 4 )3] +The cationic amines of can be prepared using any suitable method. An exemplary compound is 1-(N',N'-dimethylamino)-6,11-(N,N,N-trimethylammonium)undecane bromide, which can be synthesized in a manner similar to that described in Chen et al., Journal of Membrane Science, 552, 51-60, 15 April 2018. In the CAS Registry, this compound is listed as N 1 -[6-(Dimethylamino)hexyl]-N 1 ,N 1 ,N 5 ,N 5 ,N 5 -pentamethyl-1,5-pentanediaminium dibromide. Other compounds can be prepared in a similar manner.
[0037] The variable z represents the total mole fraction of repeat units of formula (IV) in the cationic polymer having random or block monomer repeat unit distribution, and z ranges from 0.15 to about 0.35. For example, the variable z can be at least 0.15, at least 0.20, or at least 0.25, and up to 0.30, up to 0.25, or up to 0.20.
[0038] The cationic polymer comprises repeat units of formula (I) as in the precursor polymer, i.e., the cationic polymer comprises repeat units of both formula (I) and formula (III). The cationic polymer may further contain repeat units of formula (II) if the repeat units of formula (II) have not been completely converted to repeat units of formula (III).
[0039] To prepare the cationic polymer from the precursor polymer, the precursor polymer is often dissolved in a non-polar solvent such as toluene or other non-polar solvents such as those listed above. The resulting solution of the precursor polymer is treated with a solvent of formula N(R 4 )3 or N(R 4 )2-R 5 -{[N(R 4)2 + ]-R 5} v-1 -[N(R 4 )3] + The cationic polymer is then combined with an aqueous solution containing an amine compound (with a suitable anionic counter anion). A suitable counter anion is present for the cationic group to balance the charge. The aqueous solution can contain up to 50% by weight of the amine compound dissolved in water. The resulting mixture is often mixed vigorously to form a suspension containing the cationic polymer. The suspension can be mixed, for example, at room temperature (e.g., 20-30 degrees Celsius or 25-30 degrees Celsius) to about 60 degrees Celsius for a length of time ranging from one day to about one week. The mixture containing the cationic polymer is then typically treated to remove as much liquid as possible. This can be done, for example, by filtration, using a rotavapor, or both.
[0040] In many embodiments, the counterion of the cationic polymer is bromide. If desired, an optional ion exchange reaction can be performed to replace the bromide with another anion. Suitable replacement anions include, but are not limited to, chloride, iodide, carbonate, bicarbonate, and hydroxide. In some embodiments, the anion is chloride. To perform this ion exchange, the cationic polymer is mixed with a brine solution. After mixing, the excess brine is removed by filtration, and the filtered cationic polymer is then washed. The washed cationic polymer is often filtered again. The filtered solids content is often in the range of about 10 to about 30% solids by weight.
[0041] The washed cationic polymer is often suspended in a liquid mixture of water and a polar organic solvent, such as tetrahydrofuran. Other suitable polar organic solvents include, but are not limited to, alcohols (e.g., methanol, ethanol, n-propanol, and isopropanol), and ethers (e.g., tetrahydrofuran, dimethyl ether, diethyl ether, dipropyl ether, ethylene glycol, propylene glycol, propylene glycol butyl ether, and propylene glycol dibutyl ether). The liquid mixture often has a volume ratio of water to polar organic solvent ranging from 2:1 to 1:2. The volume ratio of water to polar organic solvent can be up to 2:1, up to 1.75:1, up to 1.5:1, up to 1.25:1, or up to 1:1, and at least 1:2, at least 1:1.75, at least 1:1.5, at least 1:1.25, or at least 1:1. The suspension often contains about 1 to 20 weight percent cationic polymer. The amount can be at least 1, at least 2, at least 3, at least 5, or at least 10, and up to 20, up to 15, or up to 10 weight percent. The cationic polymer is typically swollen with the liquid in the suspension.
[0042] Suspensions containing swollen cationic polymers are often subjected to high shear mixing to break the cationic polymer into small pieces. After high shear mixing, the suspension often contains particles of cationic polymer having an average size in the range of about 10-20 micrometers, for example close to 15 micrometers. However, the particle size distribution may be as large as 100 micrometers or even larger. The size is based on the longest dimension of the particle.
[0043] The method still further includes forming a dispersion containing particles of the cationic polymer. Typically, the suspension is passed through a microfluidizer one or more times to reduce the average particle size to less than 1 micrometer (i.e., 1000 nanometers). The number of passes is often at least 1, at least 2, at least 3, at least 4, or at least 5, and up to 10, up to 8, up to 6, or up to 4. In many embodiments, two or three passes are used. The average particle size is often less than 1000 nm, less than 800 nm, less than 600 nm, less than 500 nm, less than 450 nm, and at least 200 nm, at least 250, at least 300 nm, or at least 400 nm. In some embodiments, the average particle size is in the range of 200-500 nm, in the range of 200-450 nm, or in the range of 250-450 nm.
[0044] The dispersion is typically concentrated using an ultrafiltration process, such as, for example, tangential flow filtration. Ultrafiltration can be advantageously used to remove liquids at room temperature, and the product tends to have less agglomeration compared to other processes, such as using rotavapor. After ultrafiltration, the dispersion often contains 1 to 20 weight percent, or 5 to 20 weight percent solids, based on the total weight of the dispersion. The percent solids can be at least 1, at least 2, at least 5, at least 10, or at least 15 weight percent, and up to 20, up to 15, or up to 10 weight percent, based on the total weight of the dispersion.
[0045] The method further includes preparing a coating layer from the dispersion. The coating layer is typically formed on a removable support layer. The removable support layer is a temporary substrate used to support the membrane during its manufacture. Any suitable support layer can be used. Furthermore, the coating layer may contain a reinforcing layer in addition to the cationic polymer. That is, the reinforcing layer is disposed within the coating layer.
[0046] The coating layer is typically deposited on a removable support layer. In some embodiments, the removable support layer is a release liner. The release liner is often a polymer film that can be optionally coated with a release material. Suitable polymer films include, but are not limited to, polytetrafluoroethylene (PTFE) or other synthetic polymers formed from tetrafluoroethylene, polyalkylenes (e.g., polyethylene, polypropylene, or copolymers thereof), or polyester films, such as polyethylene terephthalate. These polymer films can be optionally coated with a release material, such as a fluorinated material or a silicone material. In other embodiments, the removable support layer can be prepared, for example, from glass or any other material that can be easily separated from the coating layer after drying. That is, the removable support layer is removed before use of the membrane.
[0047] The coating layer can optionally include a porous reinforcing material in addition to the cationic polymer. That is, the coating layer can be a composite material. In order to place the porous reinforcing material in the coating layer, a first coating layer is often deposited on a removable support layer. Then, the porous reinforcing material is placed adjacent to the first coating layer on the opposite side of the removable support layer. A second coating layer is deposited such that the porous reinforcing material is placed between the first coating layer and the second coating layer. At least a portion of the coating layer composition typically absorbs the pores of the porous reinforcing material.
[0048] Suitable porous reinforcing materials include, but are not limited to, woven and nonwoven materials made from fluoropolymers such as polytetrafluoroethylene, polyethylene, polypropylene, electrospun nanofibers, glass fibers, polymeric fibers, fiber mats, perforated films, and porous ceramics. The pores of the porous reinforcing material can be imbibed (e.g., saturated or coated) with a coating layer composition. The porous support is often selected to be non-electrically conductive. The porous reinforcing material is typically relatively thin and exists for reinforcing purposes. The thickness of the porous reinforcing material can have any suitable thickness, but is often selected to be up to 10 micrometers, up to 8 micrometers, up to 6 micrometers, up to 5 micrometers, up to 4 micrometers, up to 2 micrometers, or up to 1 micrometer.
[0049] The method still further includes drying the coating layer to form a film comprising the cationic polymer. The coating layer can be dried by any suitable method. For example, the coating can be dried in a blower oven at a temperature ranging from about 65 degrees to 110 degrees Celsius. In some embodiments, the coating is dried for 30 minutes to 60 minutes.
[0050] In some embodiments, the membrane is composed primarily of the cationic polymer. In other embodiments, the membrane further comprises a porous reinforcing material embedded within the cationic polymer. That is, the membrane is a composite material containing a porous substrate and a cationic polymer.
[0051] Any removable support layer used to form the membrane is removed prior to use of the membrane.
[0052] The membrane can have any desired thickness, which is often less than 100 micrometers, less than 80 micrometers, less than 60 micrometers, less than 50 micrometers, less than 40 micrometers, less than 30 micrometers, or even less than 25 micrometers.
[0053] The membranes contain positively charged cationic polymers and can function as anion exchange membranes, and therefore can be referred to interchangeably as anion exchange membranes or polymeric anion exchange membranes.
[0054] A polymeric anion exchange membrane can have a swelling ratio, which can be characterized by the linear expansion ratio in either the chloride or hydroxide form, and which can be determined using the difference between the wet and dry dimensions of a membrane sample (e.g., a sample that is 3 cm long and 1 cm wide) using equation (1).
number
[0055] The swelling ratio in the chloride form can be less than about 60%, less than about 50%, less than about 40%, less than about 30%, less than about 20%, less than about 10%, or less than about 5%. For example, the swelling ratio can have an upper limit of about 60%, about 55%, about 50%, about 45%, about 40%, about 35%, or about 30%, and a lower limit of about 25%, about 20%, about 15%, about 10%, about 5%, or about 1%.
[0056] The swelling ratio in the hydroxide form can be less than about 90%, less than about 85%, less than about 80%, less than about 75%, less than about 70%, less than about 65%, less than about 60%, less than about 55%, less than about 50%, less than about 45%, less than about 40%, less than about 35%, or less than about 30%. For example, the swelling ratio can have an upper limit of about 90%, about 80%, about 70%, about 60%, or about 50%, and a lower limit of about 45%, about 40%, about 35%, about 30%, about 25%, about 20%, about 10%, or about 5%.
[0057] The anion exchange membrane can be placed between two electrodes of an electrochemical device, i.e., an anode and a cathode. In some embodiments, the electrode is a gas diffusion electrode that includes a catalyst-coated gas diffusion layer. Gas diffusion layers are known in the art and include, for example, carbon paper or cloth, or metal mesh.
[0058] Examples of electrochemical devices include, but are not limited to, a solid fuel cell, an electrolyzer, a chlor-alkali cell, a solid polymer electrolyte cell, a redox flow battery, or an electrochemical desalination device.
[0059] Examples of electrode materials include graphitic carbon, glassy carbon, titanium, or any of the following "catalytically active elements", namely, V, Cr, Mn, Fe, Co, Ni, Cu, Sn, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Hf, Ta, W, Re, Ir, Pt, Au, Hg, Al, Si, In, Tl, Pb, Bi, Sb, Te, U, Sm, Tb, La, Ce, Nd, and alloys or combinations thereof.
[0060] In one embodiment, the electrochemical device comprises catalytically active nanoparticles, which may be supported on carbon particles or nanostructured supports, such as carbon nanotubes or nanostructured thin films (NSTF), as disclosed, for example, in U.S. Patent No. 8,748,330 (Debe et al.).
[0061] In one embodiment, the electrochemical device comprises a surface area extended catalyst-based electrode, such as a nanostructured thin film electrode, a nanotube electrode, a porous sponge electrode, or a two-dimensional polycrystalline film electrode.
[0062] In one embodiment, the cathode of the electrochemical device comprises a metal selected from silver, gold, copper, or combinations thereof.
[0063] In one embodiment, the anode of the electrochemical device comprises a metal selected from ruthenium, iridium, platinum, titanium, or combinations thereof, In one embodiment, the electrochemical device is substantially free of platinum, meaning that the electrode comprises less than 0.1 wt%, less than 0.01 wt%, or even less than 0.001 wt% platinum.
[0064] The cathode, anode, and / or polymeric anion exchange membrane described herein can each be assembled as separate components, or can be manufactured by fabricating a polymeric ion exchange membrane (or a portion thereof) with one or both electrodes or portions thereof. For example, to maximize cost savings, and in some cases to maximize performance, the individual components or layers thereof may be thin enough that some of the components can act as supports during the fabrication of the thin layers. The various components or portions thereof can be laminated together, formed in situ on the surfaces of the components, and / or coated onto the components.
[0065] A membrane electrode assembly comprising the anode, cathode and polymeric anion exchange membrane described herein can be sandwiched between two flow field plates and then held together so that each layer is in contact, preferably in intimate contact, with the adjacent layer.
[0066] The polymeric anion exchange membrane can be used in an electrochemical device for generating electricity. The electrochemical device includes an anode, a cathode, a polymeric anion exchange membrane, a hydrogen gas input, and an oxygen gas input. The hydrogen gas input is configured to provide a composition comprising hydrogen gas to the anode flow field for oxidation of the hydrogen gas at the anode electrode. The oxygen gas input is configured to provide a composition comprising oxygen gas to the cathode flow field for reduction of the oxygen gas at the cathode electrode.
[0067] Furthermore, the polymeric anion exchange membrane can be used in an electrochemical device for electrochemically reducing carbon dioxide. The electrochemical device includes an anode, a cathode, a polymeric anion exchange membrane, and a carbon dioxide input. The carbon dioxide input is configured to provide a composition comprising carbon dioxide to the cathode flow field. Electrical energy is supplied to the electrochemical device to effect the electrochemical reduction of carbon dioxide at the cathode. To reduce carbon dioxide, the cell is operated at a positive potential difference of about 1.33 V or more, with a maximum potential difference of 4.0 V, for example, within a range of about 2.6 to about 3.4 V. EXAMPLES
[0068] All parts, percentages, ratios, etc. in the examples and elsewhere herein are by weight unless otherwise stated. Unless otherwise indicated, all other reagents were obtained or available from fine chemical suppliers such as Sigma-Aldrich Company (St. Louis, Missouri), or can be synthesized by known methods. Table 1 (below) lists the materials used in the examples and their suppliers. [Table 1]
[0069] Characterization Methods NMR of precursor polymer Portions of the precursor polymer samples were analyzed as solutions in dry deuterated chloroform, typically about 12 mg / mL. NMR spectra were acquired on a Bruker AVANCE 500 MHz NMR spectrometer equipped with a cryogenically cooled broadband probe. Monomer incorporation was determined from the peak areas associated with unique protons from each repeat unit.
[0070] Particle size measurement A PARTICALA-950 laser scattering particle size distribution analyzer (Horiba, Irvine, Calif.) was used to measure the particle size distribution of the cationic polymer before and after microfluidization.
[0071] Ionic conductivity when immersed in water The conductivity of cationic polymer membranes was measured using AC impedance spectroscopy and a four-point probe configuration with platinum wires using a Biologic MPG-205 Battery Cycler with EC-Lab V11.12 software. Samples are cut to 1 cm x 4 cm with a probe spacing of 1 cm. The instrument was operated in current control mode (AC amplitude set to 0.1 mA) with a frequency cycle of 50,000 to 1 Hz. Impedance spectra were taken and the conductivity was calculated from the resistance at the 1000 Hz data point using the following equation: Conductivity=t / (R*w*l) In this equation, conductivity is equal to conductivity (S / cm), where S refers to siemens, the unit of conductivity, t is equal to thickness (cm), w is equal to width (cm), l is equal to length (cm), and R is equal to resistance in ohms.
[0072] Conductivity measurements were performed at room temperature while samples were immersed in deionized, nitrogen-purged water. Samples in the hydroxide form were handled in a nitrogen-purged enclosure to prevent reaction with ambient carbon dioxide to form carbonate ions. Samples were usually run in duplicate or triplicate to obtain reliable average data.
[0073] Water uptake and linear swelling Water uptake and linear swelling for cationic polymer membranes were measured by measuring the mass and length of water-swollen membranes at room temperature in either chloride or hydroxide form. The samples were then dried in a 50° C. air oven for 2 hours before measuring the dry mass and length. The water uptake (wt %) and linear swelling (%) of the samples in chloride or hydroxide form, respectively, were calculated using the following equations:
number
[0074] Processing method Microfluidizer (MF) process (cationic polymer dispersion in THF / water using high shear) A portion of the swollen cationic polymer was mixed with THF and water (approximately 50:50 weight ratio) to form a slurry. A Microfluidics (Westwood, MA) Model M110-F microfluidizer with two interaction chambers (H30z 200μ and H10z 100μ) arranged in series was then filled with approximately 30 mL of the THF / water (50:50) mixture. The THF / water solution was circulated in the microfluidizer for approximately 1 minute. The polymer slurry was slowly poured into the circulating THF / water solution. After all the polymer slurry had been added to the circulating fluid, the resulting dispersion was collected and concentrated using the tangential flow filtration method described below.
[0075] Tangential flow filtration (TFF) method: TFF is a separation / concentration method in which the sample flows tangentially or parallel to the filter or membrane rather than perpendicularly. This provides a large surface area and prevents filter clogging. TFF works by applying a pressure differential across the filter while the sample flows continuously. Once appropriately sized particles / solvent (permeate) flow through the pores of the filter, the positive pressure forces the particles / solvent through the pores. The remainder of the sample (retentate) continues to flow through the system until the desired amount of permeate has passed through the filter.
[0076] Tangential flow filtration (TFF) was performed using a titanium oxide ceramic column VALISETT316L SS filtration cell EVAC025000000 from Sterlitech (Auburn, WA). The column was one channel, 250 mm long, 10 mm in diameter, with pore sizes of 100 or 300 kg / mol. Alternatively, a modified polyethersulfone hollow filter column from Spectrum Labs (Waltham, MA) was used. The column was 200 mm long with 36 fibers, giving a total fiber surface area of 1150 mm2 (mm2). 2 The inner diameter of the fiber was 0.5 mm and the pore size was 70 kg / mol.
[0077] Preparation Example Preparation Example 1 (PE1): Preparation of precursor polymer The precursor polymer was prepared by Ziegler-Natta polymerization. In a glove box, 4-phenyl-1-butene (56 mL) and 11-bromo-1-undecene (25 mL) were combined in a flask with toluene (325 mL) and gently stirred to form a monomer solution. The catalyst was prepared by mixing triisobutylaluminum (7.0 mL) and TiCl3·AA (0.6068 g) with toluene (10 mL) in a vial and stirring at room temperature for 30 minutes. The catalyst mixture was then added to the monomer solution. Toluene (10 mL) was used to rinse both the catalyst mixing vial and the top of the flask. The flask was sealed and the reaction mixture was stirred vigorously at room temperature for 24 hours. After 2 hours, the reaction mixture turned dark brown / gray and a significant amount of polymeric material was visible. After 3 hours, no further color change was observed and the sample was very viscous and almost gel-like in appearance. After 24 hours, the reaction flask was removed from the glove box and the mixture was quenched by slowly pouring into a large container of acidic methanol (1500 mL, 1 drop of concentrated HCl in 30 mL of methanol) to precipitate the polymer. The polymer was manually stirred to ensure that all surfaces were exposed to the acidic methanol. The solid polymer was redissolved in toluene (1000 mL) and reprecipitated in isopropanol (2000 mL) to remove residual monomer / catalyst. The solid polymer was filtered and dried under vacuum at 50 °C for 8-18 hours. The resulting precursor polymer was an off-white, rubbery solid with a yield of 86%. A sample of the precursor polymer was dissolved in deuterated chloroform and 1 Characterization was performed using H NMR, and the NMR data is summarized in Table 2 below. [Table 2]
[0078] The mole fraction incorporation (x) of 4-phenyl-1-butene in the precursor polymer was determined to be 79% using the following equation:
number
[0079] The mole fraction incorporation (y) of 11-bromo-1-undecene in the precursor polymer was determined to be 21% using the following equation:
number
[0080] The structures giving the NMR peaks are identified below. [ka]
[0081] Preparation Example 2 (PE2): Preparation of cationic polymer (precursor polymer PE1 quaternized with TMA) The precursor polymer PE1 was converted to a cationic polymer and dispersed in an aqueous solution prior to forming a polymer film. The precursor polymer PE1 (10.1825 g) was dissolved in toluene (250 mL) to make a 4.5 wt% solution in a 1000 mL round bottom flask at room temperature. Trimethylamine (100 mL, 50 wt% in H2O) and deionized (DI) H2O (150 mL) were then added to the rapidly stirring PE1 solution and the flask was sealed. Within the first 5-10 minutes, a polymer slurry immediately developed, after which the formation of a white precipitate was observed. The slurry was stirred at room temperature for 24 hours. The solvent and residue (TMA) were removed from the solids by rotary evaporation to obtain the water swollen quaternized polymer. The swollen quaternized polymer was ion-exchanged from the bromide anion form to the chloride anion form by placing the polymer in a saturated solution of sodium chloride (250 mL) and stirring the mixture for 30 minutes to 24 hours. The solids were filtered and this process was repeated a total of three times. The solids were rinsed several times with water and filtered to remove any excess sodium chloride. The resulting product was a white semi-solid water-swollen polymer with 29% solids by weight and a yield of 90%.
[0082] The polymer (31.62 g) was then mixed with methanol and water (50:50 mixture, 175 g) to make a 5 wt% slurry, which was then mixed in a Silverson SL2T high speed mixer (Silverson Machines, East Longmeadow, MA) to break down any large particles, followed by high shear mixing using a Microfluidizer Model M110-F (Microfluidics, Westwood, MA) to form a stable dispersion. The dispersion was passed through the Microfluidizer a total of three times, and after all the dispersion was collected, it was passed through the system again. After 48 hours, sedimentation was observed in the dispersion. The dispersion was centrifuged to separate the sediment, and the decant was filtered through a 20 micron polypropylene filter and then concentrated using tangential flow filtration technology (Sterlitech, Auburn, WA). The resulting stable PE2 dispersion was about 1.24 wt% solids. The average particle size before and after the microfiltration and tangential flow filtration processes are shown in Table 3. [Table 3]
[0083] Preparation Example 3 (PE3): Synthesis of 1-(N',N'-dimethylamino)-6,11-(N,N,N-trimethylammonium)undecane bromide (DQA) The multicationic side chain precursor was prepared in two steps before coupling to the precursor polymer. Trimethylamine (125 mL, 2 M in THF) was added to a round bottom flask at room temperature and gently stirred. To this solution was added 1,5-dibromopentane (14 mL). The graduated cylinder and top of the flask were rinsed with THF (15 mL). The flask was capped and the reaction was stirred at room temperature for 69.5 hours. The formation of a white precipitate was observed during the reaction. The white precipitate of 5-bromopentyltrimethylammonium bromide (MQA) was filtered and rinsed with THF (75 mL x 3). The solid was dried under vacuum at 50 °C for 8-18 hours to produce a white crystal consisting of very fine needles in 96% yield. A sample of the solid was dissolved in deuterated dimethyl sulfoxide and 1Characterization was performed using 1 H NMR.
[0084] Next, N,N,N',N'-tetramethyl-1,6-hexanediamine (125 mL, TMHDA) was added to acetonitrile (400 mL, ACN) in a large round bottom flask and stirred vigorously. MQA (28.00 g) was then dissolved in ACN (600 mL) in a separate flask and then slowly poured into the TMHDA / ACN solution. The flask was capped and the reaction was stirred at room temperature for 20 hours. The formation of a white precipitate was observed during the reaction. The ACN was removed from the solids on a rotary evaporator, and the solids were filtered and rinsed with hexane (50 mL x 2) to remove any residual TMHDA and ACN. The solids were dried under vacuum at 50 °C for 8-18 hours to produce a white powder consisting of very fine needle-like crystals in 62% yield. A sample of the solids was dissolved in deuterium oxide and eluted. 1 Characterization was performed using 1 H NMR.
[0085] Preparation Example 4 (PE4): Preparation of cationic polymer (precursor polymer PE1 quaternized with DQA) The precursor polymer was converted to a multicationic side chain polymer and dispersed in an aqueous solution before forming a membrane. The quaternized polymer PE4 was made using PE1 (5.07 g) and 1-(N',N'-dimethylamino)-6,11-(N,N,N-trimethylammonium)undecane bromide (DQA) (16.32 g) in toluene (160 mL) and H2O (160 mL) using the method described in Preparative Example 2. The reaction mixture was heated to 60°C for 4 days. The resulting product was a white semi-solid water-swollen polymer with 13 wt% solids and 88% yield.
[0086] The polymer is then mixed with THF and water to make a slurry, followed by high shear mixing using a microfluidizer to form a stable dispersion. The THF is mostly removed and the dispersion can be concentrated using tangential flow filtration techniques (Spectrum Labs, Waltham, MA). The resulting stable PE4 dispersion is expected to be approximately 5-10 wt% solids with a primary particle size of less than 0.5 microns. The average particle size before and after the microfiltration and tangential flow filtration processes are shown in Table 3.
[0087] Examples and Comparative Examples Example 1 (EX1): Membrane cast from PE2(TMA) An aqueous dispersion of the cationic polymer described in Preparation Example 2 (PE2) was cast to form a composite membrane consisting of the cationic polymer and an expanded poly(tetrafluoroethylene) (ePTFE) reinforced support type TX1336994-1336 (Donaldson Co., Minneapolis, MN). The porous reinforcement material, ePTFE, was attached to a polytetrafluoroethylene (PTFE) window frame and the casting side was pre-wetted with ethanol. The PE2 dispersion was slowly poured onto the wetted membrane until the inside surface of the window frame was covered. The film was placed in a blast oven and dried at 100° C. for 30 minutes. The window frame containing the film was then removed from the oven, turned over, and a second layer was cast on the opposite side of the support in the same manner as the first layer (without the pre-wetting step). The film was returned to the oven wet side up and dried at 110° C. for 45 minutes. Once dry, the film was removed from the window frame and the edges were trimmed. The resulting membranes were analyzed for conductivity, water uptake, and linear swelling in water. The resulting membranes were analyzed for conductivity, water uptake, and swelling as shown in Tables 4 and 5.
[0088] Example 2 (EX2): Membrane cast from PE4 (multication) The aqueous dispersion described in Preparative Example 4 (PE4) is cast to form a membrane having an ePTFE reinforced support using the method described in Example 1. The resulting membrane is analyzed for conductivity, water uptake, and swelling as shown in Tables 4 and 5.
[0089] Comparative Example 1 (CE1): PE1, a membrane cast from organic solvent and subsequently quaternized with TMA The precursor polymer described in Preparation Example 1 (PE1) was cast to form a composite membrane consisting of the precursor polymer and an expanded poly(tetrafluoroethylene) (ePTFE) reinforcing support. PE1 (2.52 g) was mixed with toluene (47.55 mL) to make a 5 wt % mixture. The mixture was rolled and shaken for several days until all the polymer was dissolved. The ePTFE support membrane was attached to a PTFE window frame and the casting side was pre-wetted with isopropanol. The PE1 solution was poured slowly onto the wet membrane until the inside surface of the window frame was covered. The film was placed in a blast oven and dried at 65° C. for 1 hour. The window frame with the film was then removed from the oven, turned over, and a second layer was cast on the opposite side of the support membrane in the same manner as the first layer (without the pre-wetting step). The film was returned to the oven wet side up and dried at 65° C. for 1 hour. Once dry, the film was removed from the window frame and the edges were trimmed. The film was placed in a jar containing trimethylamine (100 mL, 50 wt % H20) and rolled for 4-5 days before being removed. It was then rinsed with DI water and the film was ion-exchanged to the chloride anion form by placing it in a 2M NaCl solution (100 mL) and sonicating for 30 minutes. The solution was then exchanged and the procedure was repeated two more times. Once in the chloride form, the cationic polymer membrane was analyzed for conductivity, water uptake, and linear swelling in water. The resulting membrane was analyzed for conductivity, water uptake, and swelling as shown in Tables 4 and 5.
[0090] Comparative Example 2 (CE2): PE1, membrane cast from organic solvent and subsequently quaternized with DQA Comparative Example 2 was prepared using the method described in Comparative Example 1 with a 5 wt% dispersion of PE2 (10.15 g) and toluene (150 g) and quaternized with (1-(N',N'-dimethylamino)-6,11-(N,N,N-trimethylammonium)undecane bromide (11.15 g) dissolved in DI HO (110 mL). The film containing the quaternization solution was placed in a 60°C oven for 4 days and then ion-exchanged. The resulting membrane is analyzed for conductivity, water uptake, and swelling as shown in Tables 4 and 5. [Table 4] [Table 5]
Claims
1. 1. A method of making an anion exchange membrane comprising a cationic polymer, the method comprising: a) a precursor polymer comprising x repeating units of formula (I) and y repeating units of formula (II) 【Chemistry 1】 【Chemistry 2】 (In the formula, Each R 1 is independently aralkyl or substituted aralkyl; Each R 2 is independently an alkylene having at least 4 carbon atoms; each L is independently a leaving group; x represents the total mole fraction of repeat units of formula (I) in the precursor polymer; y represents the total mole fraction of the repeating unit of formula (II) in the precursor polymer. To prepare the following: b) reacting the repeating unit of formula (II) in the precursor copolymer with an amine compound containing a tertiary amino group to obtain a cationic polymer having a plurality of cationic repeating units of formula (III): 【Chemistry 3】 (In the formula, Each R 3 is represented by the formula {-[N(R 4 ) 2 + ]-R 5 } v -[N(R 4 ) 3 ] + Based on Each R 4 is alkyl, Each R 5 is alkylene, The variable v is an integer ranging from 0 to 10; each asterisk (*) represents a point in the precursor polymer or the cationic polymer where a repeat unit is attached to another repeat unit or to an end group; Counteranions exist to balance the charge of each cationic group. and forming c) forming a dispersion containing particles of the cationic polymer; d) preparing a coating layer from said dispersion; e) drying the coating layer to form the anion exchange membrane comprising the cationic polymer; A method comprising:
2. The amine compound containing a tertiary amino group is represented by the formula N(R 4 ) 2 -R 5 −{[N(R 4 ) 3 ] + -R 5 } v-1 -[N(R 4 ) 3 ] + 2. The method of claim 1 , wherein v is at least equal to 1.
3. The amine compound containing a tertiary amino group is represented by the formula N(R 4 ) 2 The method of claim 1 ,
4. 4. The method of any one of claims 1 to 3, wherein reacting the repeat unit of formula (II) of the precursor copolymer with the amine compound comprises forming a mixture, the mixture comprising: (a) the precursor polymer dissolved in a non-polar solvent; and (2) an aqueous solution comprising the amine compound.
5. 5. The method of any one of claims 1 to 4, wherein the dispersion is formed by passing a suspension through a microfluidizer multiple times, the suspension comprising: (a) a liquid mixture comprising water and a polar organic solvent; and (b) from 1 to 20 weight percent of a cationic polymer, based on the weight of the suspension.
6. The method of any one of claims 1 to 5, wherein the particles of the cationic polymer in the dispersion have an average particle size that is less than 1000 nanometers or less than 500 nanometers.
7. The method of any one of claims 1 to 6, wherein the dispersion containing particles of the cationic polymer has a solids content of 5 to 20 percent by weight, based on the total weight of the dispersion.
8. The method of any one of claims 1 to 7, wherein preparing the coating layer comprises disposing the coating layer adjacent to a removable support layer.
9. The method of any one of claims 1 to 8, wherein preparing the coating layer further comprises disposing a reinforcing material within the coating layer.
10. 10. The method of claim 8 or 9, further comprising removing the removable support layer after drying the coating layer.
11. The method of any one of claims 1 to 10, further comprising assembling an electrochemical device including the membrane, the membrane being disposed between an anode and a cathode of the electrochemical device.